Teachers’ Challenges in EFL Classroom Management - Reski Hidayat; La Sunra; Kisman Salija (EduLine: Journal of Education and Learning Innovation, 2024)
Every teacher who teaches a foreign language must have challenges in teaching and managing the classroom. The objectives of this study are: (1) To find out the English teachers’ challenges in English classroom management at SMA Insan Cendekia Syech Yusuf. (2) To describe the strategies used by teachers to solve the challenges in English classroom management at SMA Insan Cendekia Syech Yusuf. The subjects of this study were three teachers who taught English subjects at SMA Insan Cendekia Syech Yusuf. This research used a qualitative method. The instruments that the researcher employed were documentation, interviews, and observation. The researcher applied Miles et al.'s theory—data reduction, data display, conclusion drafting, and verification—to the data analysis process. The study's findings suggest that: (1) Teachers have difficulties when instructing pupils in English, including inadequate vocabulary acquisition, insufficient exposure to the language, psychological issues, linguistic difficulties, and low proficiency. (2) Teachers used several strategies to overcome the challenges they faced, such as the Determination Strategy, Group Discussion Strategy, and Communication Strategy. It appears that there are still a lot of difficulties in controlling and instructing English in the classroom when it comes to some of these issues. Therefore, in order to create a safe and comfortable learning environment where learning proceeds without problems teachers must employ a variety of teaching strategies in addition to appropriate classroom management techniques.